Childhood and Transnational Upbringing: The Case of Senegalese Migration to Spain - Gómez Garrido, María; Thomàs-Vanrell, Caterina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
The distribution of child care provided by people who transcend the nuclear family is a common practice in Senegalese families and in other West African countries. These forms of care play a central role in the circular migratory processes of families of Senegalese origin whose biographies are conditioned by long periods of separation, characterized by recurrent comings and goings between territories. In this study, based on 35 biographical interviews conducted in two phases, one between 2019 and 2021, and a second between 2021-2023, we detect how the effects of parental absences, in terms of material and relational resources, are mitigated by a transnational community network. Based on these results, we propose the need to consider and include the diversity of family configurations in the public policies developed in the territories of the Global North.